Food porn, pro-anorexia and the viscerality of virtual affect: Exploring eating in cyberspace - Lavis, Anna (Geoforum, 2017)
•Intersecting with work on food, affect and viscerality, this paper explores the act of eating.•The paper engages with two empirical contexts: food porn and pro-anorexia.•Geographical discussions of food are enhanced by exploring what eating does and is in cyberspace.•This reveals eating to take place among and beyond bodies, blurring boundaries of virtual and actual.•This invites further interrogation of eating’s uncertain relationship with materialities of bodies and foods, and of the act of eating more widely. By engaging with ‘pro-anorexia’ and ‘food porn’ on the Internet, this paper explores eating in cyberspace. Reflecting on the ways in which virtual, but affective, consumption is central to both food porn and pro-anorexia websites, the paper asks what the act of eating ‘triggers’ and produces, connects and displaces. It traces how eating in, and through, cyberspace shapes the biological materialities of bodies whilst also collapsing neat distinctions between offline and online worlds. Virtual vectors of spectating, salivating and digesting are disembodied and yet corporeal. Eating is seen to take place beyond and among bodies and to be dissipated both spatially and temporally. As such, cyberspace is outside and other to lived corporeality, and yet also folded into and productive of the intimate geographies and embodied subjectivities of everyday lives. As eating takes myriad forms across the de-materialised viscerality of the Internet, it also emerges as central to the production and ‘matter(ing)’ of cyberspace itself; this is (an) eating space in which what is eaten, by whom and with what bodies, perpetually shifts. Thus, seeking to contribute to geographical scholarship on affect and food, this paper engages with eating as both the subject of enquiry and also as a productive pathway into an interrogation of cyberspace and its place within the affective productions of the everyday. It suggests that this is a key site in which to explore the intimate socialities, materialities and biopolitics of food.